Prediksi Kesetimbangan Cair-Cair Sistem Pati-PVA-Air dengan metode UNIFAC - Lusiana Sri Wahyuni; Bahruddin; Ida Zahrina (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2020)
The manufacture of bioplastics by mixing PVA with starch, for example from sago, cassava, sweet potatoes, and potatoes and so on have been widely practiced. However, in some cases, blending of the polymers may not produce the desired properties due to the lack of miscibility between the mixed polymers. So that in making bioplastics a mixture of starch and PVA requires data support of the miscibility of raw materials for making bioplastics into water solvents. Miscibility can be predicted using UNIQUAC Functional - group Activity Coefficient (UNIFAC) method. The activity coefficient resulting from the UNIFAC calculation of the ternary system of starch, PVA and water shows that the activity coefficient of starch tends to increase with increasing starch composition, while the activity coefficient of PVA is not very stable. The water activity coefficient shows the opposite tendency. Temperature does not seem to have a significant effect on the composition of starch and PVA, from the calculation obtained the starch composition of 0.01045 - 0.15325 and PVA 0.38407 - 0.23860. Likewise, water shows that the heating temperature does not really affect the composition of the water. The calculation of the balance of the mixture is carried out to get the right composition for the mixture of starch, PVA and water to form a perfectly mixed mixture. The results of calculating the composition in equilibrium are shown in the ternary diagram. The diagram shows a single-phase graph, where if a mixture containing 2 components dissolves completely, it will form a single-phase region.